FEATURES OF COMBINED TREATMENT IN CHRONIC DEMODECTIC BLEPHAROCONJUNCTIVITIS - Bezditko, P.A.; Levchenko, L.I. (World of Medicine and Biology, 2020)
The article deals with the problem of treating patients with chronic demodectic blepharoconjunctivitis. Current concepts of this pathology treatment include antibacterial, anti-inflammatory, desensitizing, immunomodulatory treatment, lacrimal substitutes. The total of 80 patients (160 eyes) was examined for chronic demodectic blepharoconjunctivitis during 2016-2018 years. The combined treatment efficacy of chronic demodectic blepharitis by means of the “Metronidazole, supercritical CO2, chamomile extract, hyaluronic acid” gel drug and phototherapy device was studied. It was found that in patients with chronic demodectic blepharoconjunctivitis after combined treatment there was a decrease in eyelid edema, eyelid edges inflammation, improved secretion of meibomian glands. The biological effects of the phototherapy apparatus for the treatment of this pathology are due to such biostimulating factors as light polarization, polychromaticity, incoherence, low energy, infrared light. Secretory-stimulating, anti-inflammatory, regenerative, immunomodulatory effects were revealed. The obtained results permit to more adequately adjust the treatment of patients with chronic demodectic blepharoconjunctivitis.